2011
DOI: 10.3141/2220-03
|View full text |Cite
|
Sign up to set email alerts
|

Health Monitoring of Prestressing Tendons in Posttensioned Concrete Bridges

Abstract: Currently 90% of bridges built in California are posttensioned box girder. In such structures, the steel tendons are the main load-carrying components. The loss of prestress, as well as the presence of defects or tendon breakage, can be catastrophic for the entire structure. No well-established method monitors prestressing tendons that can provide simultaneous information related to the presence of defects and the level of prestress in a continuous, real-time manner. If such a monitoring system were available,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The guided ultrasonic wave is applied to the inspection of corrosion in pipelines and bridge tendons. This method uses vibrational characteristics of the ultrasonic wave and has been widely adopted to detect corrosion in pipelines [ 9 , 10 ]. However, it is reported that the wave experiences significant loss when penetrating concrete grouting, which causes difficulties in the measuring process [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The guided ultrasonic wave is applied to the inspection of corrosion in pipelines and bridge tendons. This method uses vibrational characteristics of the ultrasonic wave and has been widely adopted to detect corrosion in pipelines [ 9 , 10 ]. However, it is reported that the wave experiences significant loss when penetrating concrete grouting, which causes difficulties in the measuring process [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Provided that the appropriate sensing equipment and data-processing is applied, AE can provide real time volumetric information about dynamic changes related to damage. Based on this method, material damage processes at the coupon [17][18][19][20], component [21][22][23][24], and structural [25][26][27] scales have been reported. AE datasets can be further leveraged for advanced analytics such as data-driven models and machine learning [28][29][30][31][32], which may lead to a validated SHM methodology with potential even to be applied on-board, e.g., on aircraft [33].…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach is limited to being applied to bonded pre-stressing steel filled with grout. The guided wave passing through the concrete cannot be measured practically due to its attenuation in concrete [ 7 , 8 ]. As an alternative to overcome the drawbacks of ultrasonic and stress waves, a technique using a magnetic field was studied.…”
Section: Introductionmentioning
confidence: 99%